The Border Disease virus (BDV) prevalence and genetic typing in ruminant flocks in Turkey - Akman, Ayhan; Okur Gumusova, Semra (Veterinaria Italiana, 2023)
This study aims to update current data regarding Border Disease in sheep and goats, determine the first prevalence of BDV in cattle and identify its circulated genotype in Turkey. For this purpose, 100 sheep, 20 goats and 193 cattle aborted fetuses sent for diagnosis to Samsun Veterinary Control Institute between 2015 and 2017 were analyzed in terms of pestivirus by Ag‑ELISA, BDV by Real‑Time test (RT‑PCR) and Conventional RT‑PCR test. The rate of pestivirus positive animals was found at 50.26% (97/193) in cattle, 58% (58/100) in sheep and 55% (11/20) in goats by the pestivirus Ag‑ELISA test. Total of 58 Ag‑ELISA positive sheep were tested by Real‑Time RT‑PCR and conventional RT‑PCR tests. End of the tests, one sheep sample (1.72%) was found BDV positive by Real‑Time RT‑PCR test and three sheep (5.17%) and one cattle (1.03%) samples were detected as BDV positive by conventional RT‑PCR test. BDV positivity was not detected in goats in this research. All samples that were found positive by conventional RT‑PCR test and Real‑Time RT‑PCR test were genotyped by phylogenetic sequence analysis, and obtained results showed that BDV‑3 and BDV‑7 genotypes of BDV in sheep and BVDV‑1 genotype in cattle circulated in the investigated area. The sequence analysis results revealed that conventional RT‑PCR and Real‑Time RT‑PCR tests detected genotype BDV‑3, while genotype BDV‑7 was only detected by conventional RT‑PCR test in sheep abortion materials. Additionally, it was found that one bovine specimen was BDV positive by conventional PCR, but the same sample was identified as BVDV‑1 at sequence analysis. The obtained data of this study showed that new probes should be designed using our local strains for BDV diagnosis by Real‑Time RT‑PCR assay, and cattle must be sampled for BDV screening, and PCR tests results should always be confirmed by sequence analysis.